Food additives learning assistance for students at SMP Katolik Santa Clara Surabaya - Virly Virly; Netty Kusumawati; Laurensia Maria Yulian Dwiputranti Darmoatmodjo; Victor Christian Kaharso; Maria Matoetina Suprijono; Maria Magdalena Verawati (University of Merdeka Malang, 2022)
The learning assistance was designed for teachers at SMP Katolik Santa Clara to develop food additives teaching materials for theoretical learning in the classroom and work in the laboratory to give students a deeper understanding of food additives. The methods applied in this learning assistance were assistance in preparing food additives theoretical teaching materials, designing food additives laboratory works, and delivering food additives teaching materials in the classroom. In addition, laboratory work videos on borax and colorants identification in food samples were also made to facilitate independent laboratory work for students at home amid the COVID-19 pandemic. The evaluation results proved that the students gained a thorough understanding of food additives by being able to explain the definition of food additives, mention the types of food additives, identify food additives listed on food packaging, and give examples of additives misused in food products as well as its adverse impacts on health. Moreover, supplementing laboratory works could improve students' understanding of the theoretical materials and provide a new atmosphere for students to learn new knowledge. Accordingly, the food additives materials were delivered to the maximum extent to the students.